PENTINGNYA KESADARAN MASYARAKAT DAN KAPTUHAN HUKUM TERHADAP MASALAH SAMPAH DI LINGKUNGAN SEKITAR SUNGAI - Ghina Raodhatul Jannah; Aulia Rastra Faradzilla; Nasyithoh Nadratun Naim; Mahendra Putera Septyano; Khairina Laksita Nur Athifah; Nabilla Febiyanti; Kalisna Yoga Yudhistira; Perwita Chandra Puspa; Oktavia Adi Roesnia (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This study aims to analyze waste management in Indonesia from 2001 to 2022, and identify challenges and solutions that can be implemented to improve the effectiveness of waste management. Waste is a major problem affecting the environment and public health, with around 34.29% of waste in Indonesia not being managed properly. This research uses a descriptive approach by analyzing data related to policies, infrastructure, and community participation in waste management. The results showed that although there are regulations governing waste management, the main challenges faced are low public awareness and limited waste management infrastructure in many regions. The research also found that collaboration between the government, communities and the private sector is crucial in creating sustainable solutions. In addition, the development of environmentally friendly waste management technologies, such as Waste Power Plants (PLTSa), can be an innovative solution to reduce the negative impact of waste on the environment. This research suggests the need to strengthen regulations, increase public awareness, and develop more efficient and environmentally friendly waste management technologies.